PELAKSANAAN PERNIKAHAN DI BALAI NIKAH PASCA BERLAKUNYA PERATURAN PEMERINTAH NOMOR 19 TAHUN 2015 TENTANG PENERIMAAN NEGARA BUKAN PAJAK (Studi di Kantor Urusan Agama Kecamatan Ratu Agung Kota Bengkulu) - Warman, Ali (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
This study discusses the implementation of the determination of Integrated  Marriage of The formulation of this re- search  are: Firstly, how is the society’s response to the enactment of Government Regulation  No. 19 of 2015  on Non-Tax  State Revenue in the Ministry of Religious Affairs? Second, what factors cause  the community to carry out marriage  in the Central Marriage on KUA Kecamatan Ratu Agung?The  type of this research  is descriptive research  with sociological juridical approach. Data collection using interview technique, observation, documentation. This study concludes  that: Firstly, the public welcomes a positive response to the enactment of Government Regulation No. 19 of 2015. The regulation is considered as the government’s new breakthrough to discipline the marriage  cost so as to minimize illegal levies. In addition, people  with limited economic abil- ity who want to get married  is greatly helped  by the existence  of this provision.  If previously the cost of marriage  is felt by them is quite high, with this provision they can perform the marriage  for free with the condition must be implemented in the Office of Religious Affairs and at work hours. Of course this gets a positive response from the community, because it is very helpful espe- cially for the middle to lower society. Secondly,  the factors that cause the community to carry out marriage  in the marriage  hall at the Office of Religious Affairs of Ratu Agung District are economic factors and work permits. In general, informants  stated that getting married  in the Office of Religious Affairs without cost so as to ease the financial burden. In addition, the informant  was married  in the Office of Religious Affairs of Ratu Agung Sub-district due to the reason  of the work permit which was not long